The hemophiliac's motorcycle : poems - Andrews, Tom, 1961-2001 (Iowa poetry prize., 1994)
In this second wise and passionate book, Tom Andrews explores illness as a major theme, avoiding sentimentality without being merely confessional. He advances his considerable talent with great strength and forcefulness. The poems ae buoyant with humor and mindful of larger mysteries even as they investigate very personal issues. There is an urgency that is compelling; the work is immersed in the private grief of the speaker without excluding the reader.